On the Potential Role of Dietary Lysine as a Contributing Factor in Development of Liver Abscesses in Cattle - Aguiar Veloso, Vanessa; Drouillard, James S. (Frontiers in Veterinary Science, 2020)
Liver abscessation is an important metabolic disorder that commonly afflicts cattle consuming cereal-based, high-concentrate diets. Economic ramifications of liver abscessation are substantial, and include liver condemnation, decreased body weight gain, poorer efficiency of feed utilization, reduced carcass yield, and impairments in operational efficiency of commercial abattoirs. The etiological agent most commonly associated with liver abscesses is Fusobacterium necrophorum, which is an anaerobic, Gram-negative, nonmotile, nonsporulating, and rod-shaped (pleomorphic) bacterium. Fusobacterium necrophorum is one of the major proteolytic species of bacteria in the rumen, and it is believed to have a major role in degradation of dietary lysine. Herein we describe interactions between lysine and F. necrophorum, and the potential role of dietary lysine as an enabling factor in the development of liver abscesses in cattle